Development of pediatric hydronephrosis patients visiting the San Vicente Foundation University Hospital, Medellín, Colombia (2014)
ABSTRACT: Hydronephrosis is one of the most common congenital malformations detected on prenatal ultrasounds. Moderate and severe cases are often associated with urological abnormality. Objetive: To describe a series of pediatric patients diagnosed with hydronephrosis determining their etiology, prenatal diagnosis and frequency of chronic kidney disease (CKD). Materials and methods: A descriptive, retrospective study. Results: The records of 924 patients between the ages of 0 and 18 years were evaluated, 35.7% female and 64.3% male. In 14.4% (133) the diagnosis was prenatal. Hydronephrosis was bilateral in 198 patients (28.5%). In 18.3% (169) no associated urological abnormality was found, reaching 4.2% in CKD (7). Ureteropelvic stenosis was diagnosed in 23.3% (216) followed with 21.5% VUR (199) and posterior urethral valves in 9.4% (87), reaching 10.2% ERC (93). When the hydroneprhosis was diagnosed by urography, those patients presented 11.3% of chronic kidney disease vs. 8.4% in whom the diagnosis was made by ultrasound, when the hydronephosis diagnosed was by prenatal vs postnatal ultrasound, the percentage of CKD was 4.8% vs 10.8%, respectively. Conclusion:Early diagnosis of hydronephrosis allows the detection of urologic abnormalities susceptible of treatment. Although there are still many questions about which one is the ideal strategy of follow up; the ultrasonography, voiding cystourethrogram, urography, scintigraphy and magnetic resonance urography in selected patients are the most useful tools in order to evaluate urinary tract anomaly.